Comparison of the fracture resistance of endodontically treated teeth restored with prefabricated posts and composite resin cores with different post lenghts - Accácio Lins do Valle; Jefferson Ricardo Pereira; Fábio Kenji Shiratori; Luiz Fernando Pegoraro; Bonfante Gerson (University of São Paulo, 2007)
OBJECTIVE: This study evaluated the fracture strengths of endodontically treated teeth restored with prefabricated posts with different post lengths. MATERIAL AND METHODS: Thirty freshly extracted canines were endodontically treated. They were randomly divided into groups of 10 teeth and prepared according to 3 experimental protocols, as follows; Group 1/3 PP: teeth restored with prefabricated post and composite resin core (Z250) with post length of 5.0mm; Group 1/2 PP and Group 2/3 PP: teeth restored with prefabricated post and composite resin core (Z250) with different combinations of post length of 7.5mm and 10mm, respectively. All teeth were restored with full metal crowns. The fracture resistance (N) was measured in a universal testing machine (crosshead speed 0.5mm/min) at 45 degrees to the tooth long axis until failure. Data were analyzed by one-way analysis of variance (alpha=.05). RESULTS: The one-way analysis of variance demonstrated no significant difference among the different post lengths (P>.05) (Groups 1/3 PP = 405.4 N, 1/2 PP = 395.6 N, 2/3 PP = 393.8 N). Failures occurred mainly due to core fracture. CONCLUSIONS: The results of this study showed that an increased post length in teeth restored with prefabricated posts did not significantly increase the fracture resistance of endodontically treated teeth.